Risk factors of development of hepatocellular carcinoma - V. T. Ivashkin; M. A. Morozova; M. V. Mayevskaya; I. A. Sokolina; Ye. N. German; M. V. Bundina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To draw attention of general practitioners to the risk factors of hepatocellular carcinoma (HCC) development, to define group of patients with high probability of development of this tumor, to outline algorithm of screening diagnostics for patients of high risk group.Original positions of the report. Independent risk factors for HCC development include hepatitis B and C viruses, the level of hepatitis B viral load, the stage of liver cirrhosis, male gender, age over 40 years, alcohol intake and smoking. Patients of high risk group should undergo investigation of alpha-fetoprotein level and abdominal US once per 6 months for early diagnostics of HCC; at detection of any liver lesions further deep investigation including computer and magnetic-resonance tomography, guided biopsy of the lesion is indicated.Conclusion. According to present studies data, morbidity of HCC all over the world steadily grows. High risk group for HCC include patients of male gender over 50 years old (for Caucasian patients) with liver cirrhosis, especially of viral etiology, smoking and consuming alcohol. Prophylaxis of HCC should include prevention of hepatites B and C viruses infection, elimination of hepatotoxic substances, hepatitis B virus vaccination, antiviral therapy for patients with hepatites B and С. Patients from HCC risk groups need to be screened for tumor regularly (once in half a year). Its detection at the early stage allows to start medical actions in time, that helps to increase patients’ survival rate.